Focal nodular hyperplasia - Davidenko, Nicolás; Corradi, Daniel; Tiscornia, Eduardo (Cirugía del Uruguay, 1991)
which was accidenal/y found duing surgical exploration of a 36-year old fema/e with a choledochal syndrome who had taken oral contraceptives ar ten years. Echography and computerzed tomography did not show any alterations referred to the tumor. Hepatic arteiography showed ypical and characteristic alteations found by other authors in his type of tumor.